How inheriting affects bequest plans - Oded Stark; Anna Nicinska (University of Bonn, Center for Development Research (ZEF), 2015)
We present and test the idea that bequest planning is linked with the experience of inheriting. We consider "a family tradition of bequeathing" as a channel through which the intention to bequeath is molded by and is positively correlated with the experience of inheriting. We use data from the Survey on Health, Ageing, and Retirement in Europe (SHARE) to test whether, other things held constant, inheriting has a positive influence on the intention to bequeath. We find that the experience of inheriting enhances the intension to bequeath as redicted by the family tradition model, independently of the positive impact of wealth. We also find that the expectation of inheriting has a positive impact on the intention to bequeath, controlling for the expected increase in wealth on account of future inheritances. Apparently, it is not the financial means that inheritance provides which account for its impact on the intention to bequeath; it is rather the family tradition of bequeathing instilled through inheriting.
Keywords: D02; D03; D19; D64; H31; 330; intergenerational transfers; bequest behavior; experience of inheriting; expectation of inheriting; Intention to bequeath; family tradition